L’inapplicable interdiction des nations étudiantes à Toulouse (xvie‑ xviie siècle) - Patrick Ferté (Les Cahiers de Framespa)
After defining these fraternities known as « student nations », the author shows how, in Toulouse, these paralegal organizations assumed a violent mode of sociability, sowing the worst disorders in the city. Forbidden in 1530 by the Parliament and the municipality, to the despair of Étienne Dolet who set himself up as an advocate of the right of freedom of Association and friendship, they resisted for nearly a century, displaying themselves publicly, thanks to the complicity of professors and even the double play of Parliament which, on the one hand, recalled the ban but simultaneously prevented the capitouls and the watchmen from suppressing their wrongdoing and punishing the ringleader.